Análisis del Régimen Impositivo de Microempresas en el Sector de Servicios y su Incidencia en la Recaudación Tributaria en la Ciudad de Loja período 2020 – 2021. - Rodríguez Soto, Juliana Natali (2022)
The present investigation analyzed the tax regime in service microenterprises in the city of Loja, in the period 2020 - 2021, after the Organic Law of Tax Simplicity and Progressivity came into force in the country in 2019, during the crisis. caused by the pandemic caused by Covid19. The research has a mixed approach (qualitative and quantitative), where bibliographical sources were used, from the field with the objective of describing how the tax burden has affected in this sector, for this 67 companies were surveyed in the city of Loja and then The analysis of the collected data was carried out, where it was evidenced that the tax burden since the validity of the law has had an increase in microenterprises, which has triggered the closure of branches, dismissals of personnel. In the present study it was evidenced that the tax burden has caused companies to close their businesses, preside over staff, and their profits have a decrease. For this, it is important that the State generate a true policy of economic reactivation in the country that allows micro-enterprises to access credit and at the same time have preferences in various tax payments.